Identifikasi Zat Warna Rhodamin B Pada Lipstik Berwarna Merah yang Beredar Di Pasar Raya Padang - Helmice Helmice; Nila Wise Utari (STIFARM Padang, 2016)
The purpose of this study was to determine whether the red lipstick sold in the market Pasar Raya Padang containing rhodamine B. The samples were randomly taken from the market with five (5) red lipsticks samples with notification number (NA) and the other five (5) red lipsticks samples without notification number (NA). The identification of Rhodamine B in the sample by using thin layer chromatography method and the type of this research is qualitative research. The results of samples identification with thin layer chromatography method is as follow: a). Five samples of red lipstick rthat does not have notification number (NA) showed one lipstick sample (code A) containing Rhodamine B as the standard distance of Rhodamine B is equal or parallel with the difference of sample’s Rf and raw Rf less than or equal 0.2. Meanwhile the other four lipstick samples (code B, C, D, E) does not contain Rhodamine B b). Five samples of red lipstick with notification number (code F, G, H, I, and J) showed not contain Rhodamine B as Rhodamine B standard distance of and raw is not equal or not parallel with the difference between the sample’s Rf and raw Rf is more than 0.2.